2020
DOI: 10.1371/journal.pone.0230621
|View full text |Cite
|
Sign up to set email alerts
|

CD200/CD200 receptor axis in psoriasis vulgaris

Abstract: Background Psoriasis is a chronic inflammatory multisystem disease with imbalance between the Th17 and T regulatory sub-populations. CD200/CD200R is an anti-inflammatory/immune-suppressive axis that might contribute to its pathogenesis given its relation to the Tregs induction. The current study aimed to investigate the status of the CD200/CD200R axis in the blood of psoriasis vulgaris patients versus healthy controls. Methods In this comparative cross sectional study, the blood levels of sCD200 and CD200R lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, its role as a controller of inflammatory activity in EMS seems to be reduced, because the inhibitory signal of CD200 was transduced by activating the intracellular-signaling motifs of its receptor. Deficient expression of CD200R blocks the effects of the upregulated ligand, resulting in the failure of T cell polarization into a Treg subpopulation and the development of Th17, both involved in the pathogenesis of EMS [ 17 , 18 , 42 ]. Similar findings were reported by Elshal et al [ 43 ] for Th cells in inflammatory bowel disease (IBD) in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its role as a controller of inflammatory activity in EMS seems to be reduced, because the inhibitory signal of CD200 was transduced by activating the intracellular-signaling motifs of its receptor. Deficient expression of CD200R blocks the effects of the upregulated ligand, resulting in the failure of T cell polarization into a Treg subpopulation and the development of Th17, both involved in the pathogenesis of EMS [ 17 , 18 , 42 ]. Similar findings were reported by Elshal et al [ 43 ] for Th cells in inflammatory bowel disease (IBD) in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism involves the upregulation of deposits of indoleamine-pyrrole 2,3-dioxygenase (IDO), which modulates macrophage differentiation into the tolerogenic phenotype. Its overexpression may induce the depletion of local tryptophan and the production of kynurenines—tryptophan metabolites that are powerful inducers of apoptosis in cluster of differentiation 4-positive (CD4+) T cells [ 17 , 18 ]. IDO expression promotes the immunosuppressive profile of DCs and stimulates the anergic status of effector T cells [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The imbalance of Tregs/Th17 cells can be caused by the CD200–CD200R signalling pathway, which induces Treg generation and prevents Th17 differentiation, thus resulting in immune tolerance 63,64 . Moreover, the activation of the CD200/CD200R signalling pathway is also a key contributor to the Treg phenotype 65,66 . In light of the above studies, we hypothesized that PD1 hi CD200 hi CD4 + exhausted T cells may have the traits of Tregs.…”
Section: Discussionmentioning
confidence: 99%
“… 63 , 64 Moreover, the activation of the CD200/CD200R signalling pathway is also a key contributor to the Treg phenotype. 65 , 66 In light of the above studies, we hypothesized that PD1 hi CD200 hi CD4 + exhausted T cells may have the traits of Tregs. Next, our results indicated that patients with high proportions of PD1 hi CD200 low CD4 + exhausted T cells had an excellent prognosis following immunotherapy, whereas those with high proportions of PD1 hi CD200 hi CD4 + exhausted T cells demonstrated immune tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…We show reduced CD200 in PN skin, similar to previous RNAseq data. 25 Conversely, recent studies showed elevated soluble CD200 in psoriasis patient blood, 45 , 46 tempting speculation that the reduced cell‐associated CD200 in skin, may be caused by enhanced CD200 cleavage. However, the reduced CD200 mRNA levels seen (Figure 1A and previously 25 ), suggest that reduced CD200 in skin is due (at least in part) to decreased transcription.…”
Section: Discussionmentioning
confidence: 99%